The socio-economic impact of fishing communities on tourism development: A case study at Tiku Village, West Sumatra, Indonesia - Zamzami Lucky; Iwabuchi A. (BIO Web of Conferences)
The growth of the tourism industry in several regions has become evident in recent years. The tourism industry increased awareness among stakeholders, including the government, private sector, and community, regarding the impacts of these activities. The effects are noticeable in the economic sector and the social and cultural aspects of tourism destinations. While there are positive outcomes, negative impacts can also arise from tourism development, though they may be less apparent. Preventive measures are necessary to minimize these impacts. This study specifically aims to identify the socio-cultural dynamics in Tiku Village, Agam Regency. The research data was collected using a qualitative exploratory approach. The impacts of tourism development on the social life of the community in the Tiku coastal area include the transfer of land ownership, changes in land use, shifts in social perspectives, and other less significant changes that still require preventive measures to avoid adverse effects on the local society. Community empowerment is one of the strategic actions to mitigate the negative impacts of tourism activities in Tiku Village, Agam Regency.